Current Concepts in Pediatric Obstructive Sleep Apnea - Manisha Witmans; Mary Anne Tablizo (MDPI AG, 2023)
Obstructive sleep apnea (OSA) is described as intermittent partial or complete upper airway obstruction that can disrupt respiratory and ventilatory patterns during sleep [...]